Evidence-based bibliometric analysis of the journey of E-HRM research across nations - Rabindra Kumar Pradhan; Aneerban Roy (Cogent Business & Management)
Technological advancement requires the integration of information technology with HRM. However, E-HRM is complex and lacks precise information. So, we conducted an evidence-based bibliometric analysis using precise search terms from the literature to cover 229 articles from the Scopus database. We processed relevant articles on E-HRM from 2000–2023 using R software. The study highlighted that research on E-HRM is multidisciplinary, spontaneous, and discrete. It is often merged with distinct terms. There is a notable absence of extensive global collaboration. Influential authors were from developed nations. Developing nations have fallen behind in the race. Some scholars’ dominance factor and article fractionalization scores fell short of the expected level. Scholars extensively used both technology acceptance theory and institutional theory to understand E-HRM implementation. The literature is devoid of a comprehensive theory explaining its consequences. Thus, the paper describes research trends and the prominent gaps in the literature. It will add to the existing body of knowledge on E-HRM and help scholars extensively explore the phenomenon.